Constructivist Teaching Approach and Academic Achievement in Biology among Senior Secondary School Students - Aja, Lucy; Chukwuemeka, Charity; Elom, Iruka John (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
The study looked at how a constructivist-based teaching approach affected the biology academic achievement of secondary school students. This study has three research questions and three null hypotheses. The study employed a quasi-experimental research design. 853 senior secondary two students from Ebonyi local government area in Ebonyi state make up the research population. Two of thirteen coeducational secondary schools were selected using simple random sampling techniques, and 284 students were chosen for the study. The Biology Achievement Test (BAT), which has been validated by experts in measurement and evaluation as well as biology, was used to gather the data. The reliability coefficient of the instrument was 0.76 when the Kuder-Richardson formula 20 was used to evaluate its reliability. The treatment group and the control group are the two study groups. The research questions were addressed and the hypotheses were evaluated using the mean, standard deviation, and analysis of covariance. The study's findings suggest that a constructivist-based teaching strategy for instruction is a better way to encourage biology achievement. The results also demonstrate that female students outperform male students when taught using a constructivist-based teaching approach. The results also demonstrate that gender and method do not interact. According to the study, educators and biology teachers should include a constructivist-based teaching strategy in their pedagogical practices instead of relying exclusively on a conventional teaching strategy.